Analisa Pemilihan Moda Transportasi Kota Medan – Bandara Kualanamu Menggunakan Metode Analytical Hierarchy Process (AHP) - Ranto, Muhammad Aldyansyah; Fahriana, Nina; Basrin, Defry (Universitas Ibn Khaldun, 2024)
Mode of Transportation is a term for transportation user to indicate means of transportation to move from their place of origin to their destination. This mode of transportation is used to make it easier for people to move from place to place. When travelling from Medan City to Kualanamu Airport or vice versa, travellers will be faced with a choice of modes of transportation, namely rail public transportation, inter-city buses and online transportation on Medan Ciy – Kualanamu Airport route. The aim of this research was to determine the best mode of transportation chosen by passengers based on the criteria determined when travelling on the Medan City – Kualanamu Airport route and to find out which criteria had the most influence in selecting this mode. The method used in analyzing is Analytical Hierarchy Process (AHP) method. From the research result, it is known that the best mode of transpotation of choice for travelers from Medan City – Kualanamu Airpot is the Damri Bus at 52% compared to train and Train an Online Taxi which is only 24% and the most influential parameter criteria for travelers is choosing the mode of transportation for Medan City – Kualanamu Airport is a convenience level parameter of 25%, headway 19%, security 18%, comfort 16%, cost 13%, and travel time 10%.